Development Of Passing Learning Model On Volyball For Class Viii Smp Students - Rini Yatulkhusna; Safaruddin Safaruddin; Meirizal Usra; Iyakrus Iyakrus; Herri Yusfi (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2022)
AbstractThis study aims to develop a learning model of volleyball passing over for class VIII junior high school students. The research method used is research and development (research and development). The subjects in this study were eighth grade students of SMP Negeri 29 Palembang. The small group test consists of 10 students and the large group test consists of 20 students. The technique of taking the research subject used a purpose sampling technique. The results showed that the development of the volleyball passing over learning model had a material expert validity percentage level of 98%, and linguist validity 96%, so that the development of a volleyball passing over learning model could be said to be feasible. The level of reliability in the small group trial is 0.988 and the large group trial is 0.996, so it can be categorized as a high level of reliability. Overall, it is stated that the development of the volleyball passing learning model for class VIII students is very helpful for students in learning passing over more effectively. Keywords: volleyball, learning model, top passing